The Exometabolome of Two Model Strains of the Roseobacter Group: A Marketplace of Microbial Metabolites - Wienhausen, Gerrit; Noriega-Ortega, Beatriz E.; Niggemann, Jutta; Dittmar, Thorsten; Simon, Meinhard (Frontiers in Microbiology, 2017)
Recent studies applying Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) showed that the exometabolome of marine bacteria is composed of a surprisingly high molecular diversity. To shed more light on how this diversity is generated we examined the exometabolome of two model strains of the Roseobacter group, Phaeobacter inhibens and Dinoroseobacter shibae, grown on glutamate, glucose, acetate or succinate by FT-ICR-MS. We detected 2767 and 3354 molecular formulas in the exometabolome of each strain and 67 and 84 matched genome-predicted metabolites of P. inhibens and D. shibae, respectively. The annotated compounds include late precursors of biosynthetic pathways of vitamins B1, B2, B5, B6, B7, B12, amino acids, quorum sensing-related compounds, indole acetic acid and methyl-(indole-3-yl) acetic acid. Several formulas were also found in phytoplankton blooms. To shed more light on the effects of some of the precursors we supplemented two B1 prototrophic diatoms with the detected precursor of vitamin B1 HET (4-methyl-5-(β-hydroxyethyl)thiazole) and HMP (4-amino-5-hydroxymethyl-2-methylpyrimidine) and found that their growth was stimulated. Our findings indicate that both strains and other bacteria excreting a similar wealth of metabolites may function as important helpers to auxotrophic and prototrophic marine microbes by supplying growth factors and biosynthetic precursors.